Biến đổi nhân tử:
4(ab+cd)^2-(a^2+b^2-c^2-d^2)^2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) TA CÓ:
\(a^2bc^2d-ab^2cd^2+a^2bcd^2-ab^2c^2d\)
\(=abcd\left(ac-bd+ad-bc\right)\)
\(=abcd\left[a\left(c+d\right)-b\left(c+d\right)\right]\)
\(=abcd\left(c+d\right)\left(a-b\right)\)
`a^2 + ab + 2a + 2b = a(a+2) + b(a+2) = (a+b)(a+2)`
\(4\left(ab+cd\right)^2-\left(a^2+b^2-c^2-d^2\right)^2\)
\(=\left[2\left(ab+cd\right)\right]^2-\left(a^2+b^2-c^2-d^2\right)^2\)
\(=\left[2\left(ab+cd\right)-a^2-b^2+c^2+d^2\right]\left[2\left(ab+cd\right)+a^2+b^2-c^2-d^2\right]\)
\(=\left(2ab+2cd-a^2-b^2+c^2+d^2\right)\left(2ab+2cd+a^2+b^2-c^2-d^2\right)\)
\(=\left[\left(c^2+2cd+d^2\right)-\left(a^2-2ab+b^2\right)\right]\left[\left(a^2+2ab+b^2\right)-\left(c^2-2cd+d^2\right)\right]\)
\(=\left[\left(c+d\right)^2-\left(a-b\right)^2\right]\left[\left(a+b\right)^2-\left(c-d\right)^2\right]\)
\(=\left(c+d-a+b\right)\left(c+d+a-b\right)\left(a+b-c+d\right)\left(a+b+c-d\right)\)